2010
DOI: 10.1002/jssc.200900708
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic and capillary electrophoretic determination of microcystins

Abstract: Microcystins are cyclic peptide hepatotoxins that are produced during blooming of cyanobacteria. In recent two decades they gained a great interest because of the related ecological and public health risks. Over 70 different analogs of microcystins have been isolated from natural blooms and laboratory cultures of cyanobacteria. Because they are inhibitors of protein phosphatases they act as tumor promoters, but on the other hand, inhibitive enzymatic and ELISA methods may be employed for their screening or qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
(234 reference statements)
0
7
0
Order By: Relevance
“…The LC-MS technique gives reliable data with regard to detection, identification, quantification, differentiation and discovery of new MC congeners than other methods stated above [20]. For instance, it has been observed that ELISA is prone to cross-reactivity with MCs other than the MC-LR variant and thus its use is limited whenever identification and quantification of specific MC variants in samples is necessary [21,22,23,24,25]. However, the LC-MS offers complementary results for accurate detection and quantification of the same [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…The LC-MS technique gives reliable data with regard to detection, identification, quantification, differentiation and discovery of new MC congeners than other methods stated above [20]. For instance, it has been observed that ELISA is prone to cross-reactivity with MCs other than the MC-LR variant and thus its use is limited whenever identification and quantification of specific MC variants in samples is necessary [21,22,23,24,25]. However, the LC-MS offers complementary results for accurate detection and quantification of the same [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…169−171 Various columns used for preconcentration and cleanup of MCs have been exhaustively reviewed by Trojanowicz. 172 The proper selection of mobile phase (methanol based) led to better resolution of the MC-LR and -YR variants. 128 Column techniques used for the extraction and cleanup of MCs are time-consuming and require skilled personnel.…”
Section: ■ Biological Methodsmentioning
confidence: 99%
“…Rapala et al recovered several MC variants using solid phase extraction with Oasis HLB cartridges based on the cartridge’s hydrophobic-lipophilic balance. Immunoaffinity columns offered superior cleanup and selective extraction of MCs in environmental samples with trace amounts of MCs. Various columns used for preconcentration and cleanup of MCs have been exhaustively reviewed by Trojanowicz . The proper selection of mobile phase (methanol based) led to better resolution of the MC-LR and -YR variants .…”
Section: Biological Methodsmentioning
confidence: 99%
“…The plot shows an upsurge trend indicative of the increased interest and activity. Sixty eight percent (68%) of these publications came out in 2006–2010, the coverage of this review, with the following topics: pharmaceutical and herbal products applications 16–49, food and food contaminants 50–88, detection 89–103, toxicological compounds 104–111, microchips 67, 88, 112, and preconcentration 113–120. There were reviews on the general advances and new aspects of CE‐natural products analysis 15, 121, 122.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…aristolochic acids, tartaric) 80 analyzed in a wide variety of samples such as herbs, fruits, derived foods like juices, wines, and food supplements or health products. Also published were the reviews on food contaminants/natural toxins such as plant (phytotoxins), algal (phycotoxins), and the fungal (mycotoxins) 4, 50, 56, 60, 65, 66, 68, 69, 76. The most prominently researched were the mycotoxins 50, 60, 65, 68, 69, 76, with the aflatoxin and ochratoxin A, B, and C as the most notorious target analytes due to their lethal effect 50.…”
Section: Previous Reviewsmentioning
confidence: 99%